SYED MOKHTAR ALBUKHARY : A BIOGRAPHY - Mohanlall, Premilla author 312813 (Petaling Jaya, Selangor : PVm Communication, 2012)
Syed Mokhtar Albukhary is one of the most well-known tycoons in Malaysia. Yet, very little is known about the man. This biography, which is based on exclusive interviews and research by the author, offers glimpses of Syed Mokhtar's childhood and family life that imbued in him the qualities that define what he is today. A beneficiary of the New Economic Policy (NEP), the government's affirmative action programme, Syed Mokhtar made good use of the opportunities that the policy made available to bumiputera entrepreneurs. He refused to adopt the "Ali-Baba" approach of doing business with successful Chinese traders that would relegate him to the role of passive investor or rentier. Instead, he insisted on learning the ropes and became fully involved in growing the businesses that he had acquired. This toughened him to weather hard times and emerge as one of the biggest names in Malaysia's corporate landscape today. The book also highlights his good relationship with former Prime Minister Tun Dr Mahathir Mohamad, the challenges he faced during the Abdullah Ahmad Badawi years and difficulties with bad press. The frankness and forthrightness of this book makes it unusual in the Malaysian context, just like the man whose story it tells.